Otonomi Luas (Perspektif Yuridis dan Politis) - Ni'matul Huda (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2001)
Intellectual debate through the existence and the function of house representatives often measured the degree of democracy implementation, whether in Capital or Territory in a country that declared as a constitutional democracy country. In territory case, the position and the function of house of territory representatives (DPRD) are often connected with the position of territory chief. The weakness of DPRD position could be looked at the method of territory chief choice, the making of territory rule and territory chief watching. So, in autonomy era it's very important to understand the position and the function of DPRD. Here, it will be explained but just in juridical and political perspective.